Comparison of Frequency of Postoperative Nausea and Vomiting with Blend of Metoclopramide and Dexamethasone Versus Dexamethasone Alone - Ahsan, Arooj (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the frequency of postoperative nausea and vomiting with combination of Intravenous metoclopramide and dexamethasone versus Intravenous dexamethasone alone in surgeries under General Anesthesia.Study Design: Comparative prospective studyPlace and Duration of Study: Anesthesia and Intensive Care department, Combined Military Hospital, Bahawalpur Pakistan, from Oct 2020-Apr 2021.Methodology: A sample of 310 patients was collected through consecutive sampling. Patients were divided in two groups at random: Group A and Group B, by using lottery method. Group(A) patients were given combination of metoclopramide (10mg) and dexamethasone (8mg) Intravenous. Group(B) patients were given dexamethasone (8mg) Intravenous alone. After 24 hours, patients were evaluated for vomiting or nausea post-operatively.Results: The mean of age of patients in study group A was 38.87±13.07 years and in B study group was 40.10±12.13 years. Out of these 310 patients, 177(57.10%) were male and 133(42.90%) were females with male to female ratio of ratio of 1.3:1. In my study, I have found that better nausea in 14(9.03%) group A patients compared to 31(20.0%) group B patients (p-value =0.006). Vomiting was found in 03(1.94%) group A patients and 13(8.39%) in group B patients (p-value=0.010). Conclusion: This study concluded that combination of intravenous metoclopramide and dexamethasone is better as compared to intravenous dexamethasone alone in reducing nausea and vomiting post-operatively in patients receiving general anaesthesia.